The Effectiveness of Al-Miftah Lil Ulum Method in Enhancing the Ability to Read Yellow Book for Students at Zubdatul Asrar NU Islamic Boarding School in Parepare - Muh Amin; Akib; Usman; Nurhayati; Hamdanah (Universitas Muhammadiyah Palu, 2024)
This research was conducted with the aim of describing the Al-Miftah Lil Ulum method as a fast learning method for reading the yellow book for students at the Zubdatul Asrar NU Islamic Boarding School, Parepare City. The type of research used is qualitative descriptive research. The approach taken is phenomenology. The data sources for this research are primary and secondary data sources. Data collection methods are observation, interviews and documentation. Data analysis techniques using non-statistical analysis, namely by collecting, reducing, presenting and drawing conclusions. Testing the validity of the data is by reference, participation and data triangulation. The results of this research are (1) The level of ability of students in reading the yellow book is classified into three levels ranging from low, medium to high, especially new students as beginners in reading the yellow book, students still make mistakes in reading the yellow book based on the rules of nahwu and sharaf. (2) The process of using Al-Miftah Lil Ulum at the Zubdatul Asrar NU Islamic Boarding School in Parepare City takes several steps, namely: preparation, including learning objectives, materials, achievement targets, implementation. The implementation stage concerns learning time, class division and the learning process. At the evaluation stage using written and oral tests; The use of this method has worked quite well and is effective. (3) Results of the Effectiveness of Using the Al-Miftah Lil Ulum method to support the students in reading the Yellow Book well, the students can read the Yellow Book written by ulama, both classical and books written by contemporary ulama in accordance with the rules for reading books. Success and effectiveness can be seen when students succeed in advancing to class and achieve achievements in the yellow book reading competition. The first implication of this research is that future researchers can develop research on the program using the Al-Miftah Lil Ulum method which has been implemented in Islamic boarding schools. Secondly, the Al-Miftah Lil Ulum method can continue to be implemented in Islamic boarding schools, but there is still a need to provide outreach to other Islamic boarding schools regarding this method so that in the future the book reading program will be more popular among Islamic boarding schools and the community.